2018
DOI: 10.1002/jcpy.1033
|View full text |Cite
|
Sign up to set email alerts
|

Consumers Avoid Buying From Firms With Higher CEO‐to‐Worker Pay Ratios

Abstract: We document a novel driver of consumer behavior: pay ratio disclosure. Swiss corporation performance data gathered during a legally mandated pay ratio referendum reveals that salient high pay ratios are associated with decreased firm sales (Pilot Study). An incentive-compatible field experiment shows that, when ratios are revealed, consumers avoid firms with high ratios relative to competitors (Study 1). Finally, the effect of high pay ratios also depends on consumers' political ideology: Democrats and Indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 29 publications
(28 reference statements)
3
54
1
Order By: Relevance
“…Ordabayeva and Fernandes (2018) showed that political ideology affects how consumers differentiate from others, such that conservatives are more likely to choose products signaling hierarchical status whereas liberals are more likely to choose products signaling uniqueness. Mohan et al (2018) found that higher CEO-to-worker pay ratios were associated with lower consumer purchase intentions, but only among Democrats and independents. Kim, Park, and Dubois (2018) found that political ideology affects the relative motivation of maintaining status versus advancing status in the preference for luxury goods.…”
Section: Additional Social Customer Journey Considerationsmentioning
confidence: 94%
“…Ordabayeva and Fernandes (2018) showed that political ideology affects how consumers differentiate from others, such that conservatives are more likely to choose products signaling hierarchical status whereas liberals are more likely to choose products signaling uniqueness. Mohan et al (2018) found that higher CEO-to-worker pay ratios were associated with lower consumer purchase intentions, but only among Democrats and independents. Kim, Park, and Dubois (2018) found that political ideology affects the relative motivation of maintaining status versus advancing status in the preference for luxury goods.…”
Section: Additional Social Customer Journey Considerationsmentioning
confidence: 94%
“…Public pressure puts an implicit pay cap on their total annual compensation. For example, the literature (e.g., References [1,2]) discovered political and labor union pressure on CEO compensation; Mohan, Schlager, Deshpandé, and Norton [3] found that consumers avoid buying from firms with higher CEO-to-worker pay ratios. Peer pressure was also studied, for instance, for United States (US) firms versus their United Kingdom (UK) counterparts [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the distinction among these terms is integral to understanding people's reactions to uneven distributions, inequality research often lacks the necessary precision to make these distinctions clear. For example, studies which consider people's perceptions of the ideal level of CEO-to-worker ratios (e.g., Kiatpongsan & Norton, 2014) or gender wage gaps (e.g., Bessen, Meng, & Denk, 2020) may confound people's general tolerance of an uneven distribution of resources and their more specific attitudes toward inequity and fairness (see also Cappelen et al, 2007;Mohan, Schlager, et al, 2018;Son Hing et al, 2011;Starmans, Sheskin, & Bloom, 2017). Likewise, research which focuses on people's perceptions and judgments of poverty may inadvertently capture their perceptions of "needsbased inequality," that is, whether more resources should be allocated toward those that need it the most.…”
Section: What Kind Of Inequality?mentioning
confidence: 99%
“…For example, the hotly contested question of whether people underor over-perceive inequality can be re-evaluated by considering the types of inequality that people are more or less likely to underestimate (e.g., income or wealth), the unit of analysis that people bring to mind when estimating inequality (e.g., local, organizational, or national), whether people are equally prone to overestimate inequality along different areas of the distribution (e.g., how many poor there are, how rich the richest are, or disparities more broadly as captured by the Gini coefficient), and by the (implicit) reference group they bring to mind (e.g., White or Black Americans, men or women). Greater conceptual clarity can also shed light on the question of whether organizational inequality leads to more favorable (Park, Kim, & Sung, 2017;Shaw, Gupta, & Delery, 2002) or unfavorable outcomes (Benedetti & Chen, 2018;Mohan et al, 2018). These varied findings may arise in part because of different notions in the type of inequality (e.g., whether researchers operationalize inequality at the vertical level in the organization or at the horizontal level between team members) and to what extent perceived inequalities are reflective of perceived inequities (e.g., whether performance is transparently and fairly rewarded with greater salaries and bonuses).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%